Short-circuit fault location method of flexible interconnected distribution network based on waveform similarity - CHEN Jiming; CHEN Wencong; ZHANG Zhihua; YU Xinwei; XU Qian (电力工程技术)
Because of the complex control strategy and weak feed characteristics of soft normal open points (SNOP),traditional fault location methods of distribution networks are no longer applicable to flexible distribution network (FDN). A method for fault location in FDN using waveform similarity of positive-sequence current component is proposed. Firstly,considering the typical control strategy of SNOP,the short-circuit fault characteristics of FDN are analyzed. Secondly,Tanimoto coefficients of positive sequence current component at different locations are calculated. By comparing the waveform similarity at different locations of positive sequence current component,a short circuit fault location criterion for FDN is constructed. The Teager energy operator (TEO) is used to accurately calibrate the fault time,and smart terminal units (STU) are used to transmit information. Finally,the proposed method is analyzed and verified through modeling and simulation. The results show that the proposed method can accurately locate the fault section,and has the ability to resist the influence factors such as fault location,fault type,transition resistance,sampling frequency and communication delay,which verifies the feasibility and effectiveness of the proposed method.